Analysis of the Implementation of the Indonesian National Army (TNI AD) Territorial Development Policy to Prevent Social Conflict - Fitrianang, Very Grahita; Soeling, Pantius Drahen (Publik : (Jurnal Ilmu Administrasi), 2023)
The implementation of the Indonesian National Army - Ground Forces (TNI - AD) Territorial Development Policy is based on the policy implementation process approach, which has several dimensions, namely size and objectives, resources, characteristics of implementing agencies, communication, disposition, social, economic, and political environment. The importance of this research lies in better understanding the effectiveness of the Indonesian Army's territorial development policies in preventing social conflict, which can help in designing more effective strategies to maintain social stability in the region. By identifying successes and weaknesses in implementing the TNI AD's territorial development policy, it is hoped that it can provide critical insight for policymakers in increasing social stability in the region. This research aims to analyze the implementation and impact of the TNI AD's territorial development policy in preventing social conflict. This research uses a post-positivism paradigm with qualitative methods. The data collection techniques used are in-depth interviews and document studies. The result is the Implementation of the Army Territorial Development Policy for the prevention of social conflict in Kodim 0618 / Bandung City, and the researcher concluded that the implementation of the policy has not been carried out optimally because it has experienced several obstacles. Lack of clear information about territorial development to the TNI and the community, information that is not clear enough can complicate understanding of territorial development. The low human resource factor can cause obstacles in the implementation.